Non-aqueous electrolyte storage element

By employing solid graphite particles with a low aspect ratio and an optimal amount of unsaturated cyclic carbonate, the nonaqueous electrolyte storage elements achieve sustained high output characteristics over long-term use, addressing the issue of deteriorating performance in conventional systems.

JP7666502B2Active Publication Date: 2025-04-22GS YUASA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022507230
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-12
Filing Date
2021-03-10
Publication Date
2025-04-22
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

Conventional nonaqueous electrolyte storage elements with graphite negative electrodes suffer from deteriorating output characteristics over long-term use due to the decomposition of unsaturated cyclic carbonates, leading to inadequate edge surface coverage and increased consumption.

Method used

The use of solid graphite particles with a low aspect ratio and an appropriate amount of unsaturated cyclic carbonate in the nonaqueous electrolyte, ensuring a moderate and uniform coating on the graphite particles, thereby maintaining high output characteristics after long-term use.

Benefits of technology

This approach results in nonaqueous electrolyte storage elements with solid graphite negative electrodes that maintain high output characteristics even after extended use, as the moderate and uniform coating effectively suppresses the deterioration of performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666502000002
    Figure 0007666502000002
  • Figure 0007666502000003
    Figure 0007666502000003
  • Figure 0007666502000004
    Figure 0007666502000004
Patent Text Reader

Abstract

This nonaqueous electrolyte power storage element according to one embodiment comprises: a negative electrode having a negative electrode active material layer; and a nonaqueous electrolyte containing unsaturated cyclic carbonate. The negative electrode active material layer contains solid graphite particles having an aspect ratio of 1 to 5. The amount of the unsaturated cyclic carbonate with respect to the surface area of the negative electrode active material is 0.03 mmol / m2 to 0.08 mmol / m2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.

[0003] A typical example of a non-aqueous electrolyte storage element is one having electrodes (positive and negative electrodes) in which an active material layer containing an active material is laminated on an electrode substrate. Carbon materials such as graphite are widely used as the negative electrode active material (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2005-222933 Summary of the Invention [Problem to be solved by the invention]

[0005] One of the requirements for a nonaqueous electrolyte storage element is that it is highly durable and maintains high performance for a long period of time. Conventional nonaqueous electrolyte storage elements have a negative electrode containing graphite as a negative electrode active material, and output characteristics deteriorate with long-term use. Therefore, improvement in durability is desired.

[0006] The present invention has been made in light of the above circumstances, and has an object to provide a nonaqueous electrolyte electricity storage element having a negative electrode containing graphite, which has high output characteristics even after long-term use. [Means for solving the problem]

[0007] A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode having a negative electrode active material layer, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, the negative electrode active material layer containing solid graphite particles having an aspect ratio of 1 or more and 5 or less, and an amount of the unsaturated cyclic carbonate relative to a surface area of ​​the negative electrode active material layer is 0.03 mmol / m 2 More than 0.08mmol / m 2 The nonaqueous electrolyte electricity storage element is as follows: Effect of the Invention

[0008] According to one aspect of the present invention, there is provided a nonaqueous electrolyte electricity storage element including a negative electrode containing graphite, which has high output characteristics even after long-term use. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic perspective view showing an electricity storage element (nonaqueous electrolyte electricity storage element) according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of electricity storage elements (nonaqueous electrolyte electricity storage elements) according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a graph showing the evaluation results of each of the nonaqueous electrolyte storage elements of the examples and comparative examples in which graphite particles A (solid graphite particles) or graphite particles B (hollow graphite particles) were used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.

[0011] A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode having a negative electrode active material layer, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, the negative electrode active material layer containing solid graphite particles having an aspect ratio of 1 or more and 5 or less, and an amount of the unsaturated cyclic carbonate relative to a surface area of ​​the negative electrode active material layer is 0.03 mmol / m 2 More than 0.08mmol / m 2 The nonaqueous electrolyte electricity storage element is as follows:

[0012] The nonaqueous electrolyte storage element according to one embodiment of the present invention is a nonaqueous electrolyte storage element having a negative electrode containing graphite, and has high output characteristics even after long-term use. The reason for this is unclear, but is presumed to be as follows. Conventionally, graphite particles used as negative electrode active materials are often hollow or have a high aspect ratio, and the edge surface is highly exposed. In order to improve durability, etc., an unsaturated cyclic carbonate such as vinylene carbonate that decomposes during charging to form a coating on the particle surface of the negative electrode active material may be added to the nonaqueous electrolyte of the nonaqueous electrolyte storage element. When graphite particles with a high edge surface exposure are used, the consumption amount due to continuous decomposition of the unsaturated cyclic carbonate accompanying long-term use is large. Therefore, in order to sufficiently cover the edge surface of the graphite particles and suppress the decrease in output characteristics after long-term use, it is necessary to increase the amount of unsaturated cyclic carbonate added. However, if the amount of unsaturated cyclic carbonate is large, a thicker coating than necessary may be formed locally on the edge surface of the graphite particles during initial charging and discharging, or a thicker coating may be formed on parts other than the edge surface, and so on, which may result in a decrease in output characteristics immediately after the initial charging and discharging. For this reason, when conventional general graphite particles are used, it is difficult to improve the output characteristics after long-term use even if the amount of unsaturated cyclic carbonate added is adjusted. In contrast, the graphite particles used in the nonaqueous electrolyte storage element according to one embodiment of the present invention have a low aspect ratio and a solid shape, and the exposure degree of the edge surface is low. When such graphite particles are used, even if a relatively small amount of unsaturated cyclic carbonate is added, a coating that can sufficiently cover the edge surface of the graphite particles can be formed, and the consumption due to continuous decomposition of the unsaturated cyclic carbonate accompanying long-term use is also small. That is, in a nonaqueous electrolyte storage element according to one embodiment of the present invention, solid graphite particles having a low aspect ratio are used, and the amount of unsaturated cyclic carbonate present in the nonaqueous electrolyte is within an appropriate range that is not excessive relative to the surface area of ​​the negative electrode active material layer, so that a coating derived from the unsaturated cyclic carbonate is formed with an appropriate thickness and high uniformity over the entire surface of the solid graphite particles.For these reasons, it is presumed that the nonaqueous electrolyte electricity storage element according to one embodiment of the present invention will have high output characteristics even after long-term use.

[0013] In addition, "graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Here, the "discharged state" refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode. Since the potential of the metal Li counter electrode in the open circuit state is approximately equal to the oxidation-reduction potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the oxidation-reduction potential of Li. In other words, the open circuit voltage of the single-electrode battery being 0.7 V or more means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0014] Moreover, the term "solid" in solid graphite particles means that the inside of the particle is filled and substantially no voids exist. More specifically, "solid" means that in a cross section of the particle observed in an SEM image obtained using a scanning electron microscope (SEM), the area ratio excluding voids within the particle to the entire particle area is 95% or more. In a preferred embodiment, the area ratio of the solid graphite particles can be 97% or more (e.g., 99% or more). The area ratio of the graphite particle excluding the voids in the particle to the total particle area can be determined by the following procedure. (1) Preparation of the measurement sample The graphite particle powder to be measured is fixed in a thermosetting resin. A cross-section polisher is used to expose the cross section of the graphite particle fixed in the resin, and the measurement sample is prepared. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 3 to 15 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Cutting out the outline of the graphite particles The image cutting function of the image editing software Adobe Photoshop Elements 11 is used to cut out the outlines of the graphite particles from the acquired SEM image. This cutting out of the outlines is performed by using the quick selection tool to select the area outside the outlines of the graphite particles, and then editing everything except the graphite particles to a black background. If the outlines of less than three graphite particles could be cut out at this time, another SEM image is acquired and the process is repeated until the outlines of three or more graphite particles can be cut out. (4) Binarization The image of the first graphite particle among the cut-out graphite particles is binarized using the image analysis software PopImaging 6.00, with a threshold value set to a concentration 20% lower than the concentration at which the intensity is at its maximum. The area of ​​the lower concentration side is calculated through the binarization process, and this is taken as the "area S1 excluding voids within the particle." Next, the image of the first graphite particle, the same as before, is subjected to a binarization process with a threshold density of 10. Through the binarization process, the outer periphery of the graphite particle is determined, and the area inside the outer periphery is calculated to obtain the "area S0 of the entire particle." Using the S1 and S0 calculated above, the ratio of S1 to S0 (S1 / S0) is calculated to calculate the "area ratio T1 excluding voids within the particle to the entire particle area" for the first graphite particle. The above binarization process is also performed on the images of the second and subsequent graphite particles among the cut-out graphite particles, and the areas S1 and S0 are calculated. The area ratios T2, T3, ... of each graphite particle are calculated based on the calculated areas S1 and S0. (5) Determination of area ratio The average value of all the area ratios T1, T2, T3, ... calculated by the binarization process is calculated to determine the "area ratio of graphite particles excluding voids within the particles to the entire particle area."

[0015] The "aspect ratio" refers to the A / B value, which is the ratio of the longest diameter A of a particle to the longest diameter B in the direction perpendicular to diameter A, in the cross section of the particle observed in an SEM image obtained using a scanning electron microscope. The aspect ratio can be determined as follows. (1) Preparation of the measurement sample A measurement sample is used in which the cross section used in determining the above-mentioned area ratio is exposed. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 100 to 1000 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Determining the aspect ratio From the acquired SEM image, 100 graphite particles are randomly selected, and for each, the longest diameter A of the graphite particle and the longest diameter B in the direction perpendicular to diameter A are measured, and the A / B value is calculated. The aspect ratio of the graphite particle is determined by calculating the average value of all the calculated A / B values.

[0016] The "amount of unsaturated cyclic carbonate" refers to the amount of unsaturated cyclic carbonate contained in the nonaqueous electrolyte of the nonaqueous electrolyte storage element, and is not the amount of unsaturated cyclic carbonate contained in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte storage element. The nonaqueous electrolyte storage element according to one embodiment of the present invention is completed through initial charging and discharging, and a part of the unsaturated cyclic carbonate contained in the nonaqueous electrolyte used in the manufacture decomposes during the initial charging and discharging to form a coating on the particle surface of the negative electrode active material. Therefore, although there is a certain degree of correlation between the amount of unsaturated cyclic carbonate contained in the nonaqueous electrolyte used in the manufacture and the amount of unsaturated cyclic carbonate contained in the nonaqueous electrolyte of the nonaqueous electrolyte storage element completed through the initial charging and discharging, they do not coincide. Specifically, the "amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer" is measured by the following method. (1) Measurement of the amount of unsaturated cyclic carbonate in non-aqueous electrolyte The mass A of the nonaqueous electrolyte storage element is measured. Then, the nonaqueous electrolyte storage element is disassembled, and the nonaqueous electrolyte is collected. All parts other than the nonaqueous electrolyte are washed with dimethyl carbonate and thoroughly vacuum dried. The mass B of all parts other than the nonaqueous electrolyte after vacuum drying is measured. The difference between mass A and mass B is the mass C of the nonaqueous electrolyte contained in the nonaqueous electrolyte storage element. Meanwhile, the concentration (mass%) of the unsaturated cyclic carbonate in the nonaqueous electrolyte is obtained by GC-MS analysis using the nonaqueous electrolyte collected during disassembly. The mass D of the unsaturated cyclic carbonate in the nonaqueous electrolyte is calculated from the concentration of the unsaturated cyclic carbonate and the mass C of the nonaqueous electrolyte. The mass D of the unsaturated cyclic carbonate in the nonaqueous electrolyte is divided by the molecular weight of the unsaturated cyclic carbonate to obtain the amount of substance of the unsaturated cyclic carbonate in the nonaqueous electrolyte. The structural formula, molecular weight and concentration of the unsaturated cyclic carbonate can be determined by comparing the results of GC-MS analysis under the same conditions of a calibration curve sample containing an unsaturated cyclic carbonate of known structural formula and concentration. (2) Measurement of the surface area of ​​the negative electrode active material layer A predetermined area of ​​the negative electrode active material layer is collected from the negative electrode that has been disassembled, washed and vacuum dried when the amount of the unsaturated cyclic carbonate is measured. The mass of the collected negative electrode active material layer is measured to determine the mass of the negative electrode active material layer per unit area. The mass E of the negative electrode active material is calculated from the mass of the negative electrode active material layer per unit area and the area of ​​the negative electrode active material layer provided on the negative electrode. The "area of ​​the negative electrode active material layer" here is defined as the area of ​​the portion facing the positive electrode active material layer via the separator. Meanwhile, the BET specific surface area is measured by the nitrogen adsorption method using the portion of the negative electrode that was not used to calculate the mass E of the negative electrode active material. This measurement can be performed using "autosorb iQ" manufactured by Quantachrome. Five points are extracted from the region of P / P0=0.06 to 0.3 of the obtained adsorption isotherm, and a BET plot is performed, and the BET specific surface area is calculated from the y-intercept and slope of the straight line. The product of the BET specific surface area and the mass E of the negative electrode active material layer is the surface area of ​​the negative electrode active material layer. (3) Calculation of the amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer The amount of the unsaturated cyclic carbonate in the non-aqueous electrolyte determined in (1) is divided by the surface area of ​​the negative electrode active material layer determined in (2) to determine the amount of the unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer.

[0017] The solid graphite particles preferably have an average particle size of 2 μm or more and 6 μm or less. By using solid graphite particles with a relatively small particle size in this way, the negative electrode active material layer is densified, the surface area of ​​the solid graphite particles is increased, and electrical conductivity is increased, thereby improving the output characteristics even after long-term use.

[0018] The term "average particle size" refers to the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by the laser diffraction / scattering method for a diluted solution in which particles are diluted with a solvent in accordance with JIS-Z-8825 (2013). Specifically, the measured value can be determined by the following method. Measurements are performed using a laser diffraction particle size distribution analyzer (Shimadzu Corporation's "SALD-2200") as the measuring device and Wing SALD II as the measurement control software. A scattering measurement mode is adopted, and a laser beam is irradiated onto a wet cell in which a dispersion liquid in which the measurement sample is dispersed in a dispersion solvent is circulated, and the scattered light distribution from the measurement sample is obtained. The scattered light distribution is then approximated by a log-normal distribution, and the particle size at which the cumulative degree is 50% is taken as the average particle size (D50).

[0019] It is preferable that the negative electrode active material contained in the negative electrode active material layer is substantially only the solid graphite particles. In this way, when substantially only solid graphite particles are used as the negative electrode active material, the advantage of using the solid graphite particles is effectively exhibited, and the output characteristics after long-term use are further improved.

[0020] Here, "the negative electrode active material contained in the negative electrode active material layer is substantially only the solid graphite particles" means that the content of the solid graphite particles in the total negative electrode active material contained in the negative electrode active material layer is 99 mass % or more.

[0021] It is preferable that the negative electrode active material layer is not pressed. In conventional non-aqueous electrolyte storage elements, the negative electrode active material layer is generally pressed in the manufacturing process in order to increase density and improve adhesion to the substrate. However, when the negative electrode active material layer containing graphite particles is pressed, cracks in the graphite particles occur, and the edge surface of the graphite particles is exposed to a high degree, which tends to reduce the output characteristics after long-term use. Therefore, by not pressing the negative electrode active material layer, the output characteristics after long-term use can be further improved. In addition, in the non-aqueous electrolyte storage element, by using solid graphite particles, the negative electrode active material layer can have a sufficiently high density without being pressed.

[0022] Here, "not pressed" means that during production, a process of applying a pressure (linear pressure) of 10 kgf / mm or more to the negative electrode active material layer using a device intended to apply pressure to a workpiece, such as a roll press, is not performed. In other words, "not pressed" also includes a process in which a slight pressure is applied to the negative electrode active material layer in other processes, such as winding the negative electrode. "Not pressed" also includes a process in which a pressure (linear pressure) of less than 10 kgf / mm is applied.

[0023] A nonaqueous electrolyte storage element according to one embodiment of the present invention and other embodiments will be described in detail below. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.

[0024] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element according to one embodiment of the present invention includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode and the negative electrode are usually stacked or wound with a separator interposed therebetween to form an electrode assembly. This electrode assembly is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also simply referred to as a "secondary battery") will be described.

[0025] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer laminated on the positive electrode substrate directly or via an intermediate layer, which is another layer.

[0026] (Positive electrode substrate) The positive electrode substrate is a substrate having electrical conductivity. The term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7This means that the resistance is Ω·cm or less. Metals such as aluminum, titanium, tantalum, and stainless steel, or alloys thereof, are used as the material for the positive electrode substrate. Among these, aluminum or aluminum alloys are preferred in terms of the balance between potential resistance, high conductivity, and cost. Examples of the form of the positive electrode substrate include foil and evaporated film, and foil is preferred in terms of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085 and A3003, etc., as specified in JIS-H-4000 (2014).

[0027] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per volume of the secondary battery. The "average thickness" of the positive electrode substrate refers to the value obtained by dividing the mass of the substrate of a given area by the true density and area of ​​the substrate. The "average thickness" is defined similarly when used for the negative electrode substrate.

[0028] (Middle class) The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a resin binder and conductive particles (conductive agent). It is preferable that the intermediate layer further contains a crosslinking agent. The intermediate layer may cover a part of the positive electrode substrate or may cover the entire surface.

[0029] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.

[0030] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Mn 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al 1-x-γ-β ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn 2-γO4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.

[0031] As the positive electrode active material, a polyanion compound is preferable, and lithium iron phosphate is more preferable. The lithium iron phosphate may be LiFePO4 or a compound in which a part of LiFePO4 is replaced with other atoms or other anion species. When the positive electrode active material is such a compound, the progress of the performance deterioration of the secondary battery with long-term use is largely dependent on the negative electrode active material. Therefore, in the secondary battery (nonaqueous electrolyte storage element) according to one embodiment of the present invention, when the positive electrode active material is such a compound, the effect of high output characteristics even after long-term use is particularly remarkable.

[0032] The positive electrode active material is usually a particle (powder). The average particle diameter of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle diameter of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle diameter of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. When a composite of the positive electrode active material and another material is used, the average particle diameter of the composite is taken as the average particle diameter of the positive electrode active material.

[0033] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0034] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0035] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0036] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0037] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0038] The binder content in the positive electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 9% by mass (for example, 3% by mass to 6% by mass). By setting the binder content in the above range, the active material can be stably held.

[0039] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the ratio of the thickener to the entire positive electrode active material layer can be about 8 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less). The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the thickener.

[0040] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the proportion of the filler in the entire positive electrode active material layer can be about 8.0 mass% or less, and is usually about 5.0 mass% or less (for example, 1.0 mass% or less). The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the filler.

[0041] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0042] The density of the positive electrode active material layer is not particularly limited, and may be, for example, 1.0 g / cm 3 More than 3.0g / cm 3 Less than 1.5 g / cm is preferred. 3 More than 2.5g / cm 3 The following is more preferred:

[0043] The density of the positive electrode active material layer is the mass per unit area of ​​the positive electrode active material layer (g / cm 2) divided by the average thickness (cm). The average thickness of the positive electrode active material layer is the average value of thicknesses measured at five positions on ten positive electrodes cut into 2 cm x 2 cm pieces. The thickness of the positive electrode active material layer can be measured using a high-precision digimatic micrometer manufactured by Mitutoyo Corporation. The same applies to the density and average thickness of the negative electrode active material layer described below.

[0044] The average thickness of the positive electrode active material layer (when the positive electrode active material layer is formed on both sides of the positive electrode substrate, the total thickness of both sides) is not particularly limited, but for example, the lower limit is preferably 20 μm, more preferably 30 μm, and even more preferably 40 μm. On the other hand, the upper limit of the average thickness of the positive electrode active material layer is, for example, preferably 200 μm, more preferably 120 μm, more preferably 80 μm, and even more preferably 70 μm.

[0045] [Negative electrode] The negative electrode has a negative electrode substrate and a negative electrode active material layer laminated on the negative electrode substrate directly or via an intermediate layer, which is another layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0046] (Negative electrode substrate) The negative electrode substrate is a substrate having electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel or alloys thereof are used as the material of the negative electrode substrate, and copper or a copper alloy is preferred. The form of the negative electrode substrate may be a foil, a vapor deposition film, or the like, and foil is preferred from the viewpoint of cost. That is, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0047] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.

[0048] (Negative electrode active material layer) The negative electrode active material layer contains solid graphite particles having an aspect ratio of 1 to 5. The solid graphite particles function as a negative electrode active material. The negative electrode active material layer contains optional components such as other negative electrode active materials, binders, conductive agents, thickeners, and fillers as necessary. The optional components such as binders, conductive agents, thickeners, and fillers can be selected from the materials exemplified for the positive electrode above.

[0049] The solid graphite particles can be appropriately selected from various known graphite particles and used. Examples of such known graphite particles include natural graphite particles and artificial graphite particles. Here, natural graphite is a general term for graphite extracted from natural minerals, and artificial graphite is a general term for graphite produced artificially. Specific examples of natural graphite particles include flake graphite, lump graphite (flake graphite), and earthy graphite. The solid graphite particles can be spherical natural graphite particles obtained by spheroidizing flat flake graphite. As the solid graphite particles, natural graphite particles or artificial graphite particles may be used, but artificial graphite particles are preferred. In general, artificial graphite particles have a smaller specific surface area and less exposed edge surfaces compared to natural graphite particles. For this reason, the use of artificial graphite particles increases durability and improves output characteristics after long-term use. The graphite particles may also be graphite particles having a coating (eg, an amorphous carbon coating) on ​​the surface.

[0050] The aspect ratio of the solid graphite particles is 1 or more and 5 or less, preferably 2 or more and 4 or less. By setting the aspect ratio of the solid graphite particles within the above range, particularly below the upper limit, the solid graphite particles become closer to a sphere, a highly homogeneous coating is formed by the unsaturated cyclic carbonate, and current concentration is less likely to occur, improving the output characteristics after long-term use. In some embodiments, the aspect ratio of the solid graphite particles may be 2.2 or more (e.g., 2.5 or more, e.g., 2.7 or more). In some embodiments, the aspect ratio of the solid graphite particles may be 3.5 or less (e.g., 3.0 or less).

[0051] The solid graphite particles may be, for example, spherical or non-spherical. Specific examples of non-spherical shapes include chunks, spindles, flakes, plates, ellipses, and eggs. Among these, chunks of solid graphite particles are preferred. The solid graphite particles may have irregularities on the surface. The solid graphite particles may include particles formed by agglomeration of a plurality of graphite particles.

[0052] The average particle size of the solid graphite particles may be, for example, 0.1 μm to 30 μm (typically 0.3 μm to 25 μm), but is preferably 0.5 μm to 15 μm, more preferably 1 μm to 10 μm, even more preferably 2 μm to 6 μm, and even more preferably 2.5 μm to 4 μm. By setting the average particle size of the solid graphite particles within the above range, particularly below the above upper limit, the surface area is increased, the conductivity is increased, and the output characteristics after long-term use are further improved. In addition, by setting the average particle size of the solid graphite particles to the above lower limit or more, the ease of handling during production can be improved. Suitable examples of the solid graphite particles disclosed herein include those having an average particle size (D50) of 5 μm or less and an aspect ratio of 1 to 5; those having an average particle size (D50) of 4.5 μm or less and an aspect ratio of 1.5 to 4.5; those having an average particle size (D50) of 4 μm or less and an aspect ratio of 1.8 to 4; those having an average particle size (D50) of 3 μm or less and an aspect ratio of 2 to 3.5; etc. By using solid graphite particles having an aspect ratio and average particle size (D50) within such a predetermined range, the above-mentioned effects can be better exhibited.

[0053] The true density of solid graphite particles is 2.1 g / cm 3 The use of solid graphite particles having such a high true density makes it possible to increase the energy density. On the other hand, the upper limit of the true density of the solid graphite particles is, for example, 2.5 g / cm 3 The true density is measured by a gas volumetric method using a pycnometer with helium gas. The BET specific surface area of ​​the solid graphite particles is not particularly limited, but is, for example, 3 m 2 / g or more. By using solid graphite particles having such a large BET specific surface area, the above-mentioned effects can be more effectively exhibited. The BET specific surface area of ​​the solid graphite particles is preferably 3.2 m 2 / g or more, more preferably 3.5m 2 / g or more, more preferably 3.7m 2 The upper limit of the BET specific surface area of ​​the solid graphite particles is, for example, 10 m 2 The solid graphite particles preferably have a BET specific surface area of ​​8 m 2 / g or less, more preferably 6m 2 / g or less, more preferably 5m 2 The BET specific surface area of ​​solid graphite particles is determined by measuring the pore size distribution by the single-point method using nitrogen gas adsorption.

[0054] The R value of the solid graphite particles can be generally 0.25 or more (e.g., 0.25 to 0.8), for example, 0.28 or more (e.g., 0.28 to 0.7), typically 0.3 or more (e.g., 0.3 to 0.6). In some embodiments, the R value of the solid graphite particles may be 0.5 or less, or may be 0.4 or less. Here, the "R value" refers to the peak intensity of the G band in the Raman spectrum (I G1 ) versus D band peak intensity (I D1 ) ratio (I D1 / I G1 ).

[0055] The above Raman spectrum is obtained by performing Raman spectroscopy using Horiba's "HR Revolution" under the conditions of a wavelength of 532 nm (YAG laser), a grating of 600 g / mm, and a measurement magnification of 100 times. -1 From 4000cm -1 Raman spectroscopy was performed in the range of 4000cm -1 The minimum value in the range is taken as the base intensity, and normalized by the maximum intensity in the above measurement range (for example, the intensity of the G band). Next, the obtained curve is fitted using a Lorentz function, and the 1580 cm-1 Nearby G band and 1350 cm -1 The intensity of each of the D bands in the vicinity was calculated, and the "G band peak intensity (I G1 ) and D band peak intensity (I D1 )".

[0056] The solid graphite particles in the negative electrode active material layer of the negative electrode included in the secondary battery (nonaqueous electrolyte storage element) according to one embodiment of the present invention usually have a coating formed on the surface. This coating is usually formed by performing initial charging and discharging in the manufacturing process. This coating is usually a coating derived from an unsaturated cyclic carbonate added to the nonaqueous electrolyte used during manufacturing, and may be a coating derived from the unsaturated cyclic carbonate and other components.

[0057] The negative electrode active material layer may contain other negative electrode active materials other than solid graphite particles, so long as the effects of the present invention are not impaired. Examples of other negative electrode active materials include carbonaceous materials other than solid graphite particles, metals such as Si and Sn, oxides of these metals, or composites of these metals with carbonaceous materials. Examples of carbonaceous materials other than solid graphite particles include hollow graphite particles and non-graphitic carbon. "Hollow graphite particles" are graphite particles other than solid graphite particles. "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials. The term "non-graphitizable carbon" refers to a carbonaceous material having the above-mentioned d 002 The term "easily graphitizable carbon" refers to a carbon material having a particle size of 0.36 nm or more and 0.42 nm or less. 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0058] The lower limit of the content ratio of solid graphite particles to all the negative electrode active materials contained in the negative electrode active material layer may be 50% by mass or 70% by mass, but is preferably 90% by mass, more preferably 95% by mass, even more preferably 99% by mass, and even more preferably 99.9% by mass. The upper limit of the content ratio of solid graphite particles to all the negative electrode active materials contained in the negative electrode active material layer may be 100% by mass. In this way, it is preferable that the negative electrode active material contained in the negative electrode active material layer is substantially only solid graphite particles. When substantially only solid graphite particles are used as the negative electrode active material, the output characteristics after long-term use are further improved.

[0059] The content of the solid graphite particles in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 80% by mass to 98% by mass, and even more preferably 90% by mass to 97% by mass. The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 80% by mass to 98% by mass, and even more preferably 90% by mass to 97% by mass. By setting the content of the solid graphite particles and the negative electrode active material in the above ranges, it is possible to further improve the output characteristics after long-term use, the energy density of the negative electrode active material layer, manufacturability, and the like.

[0060] The content of the binder in the negative electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 3% by mass to 9% by mass. By setting the content of the binder in the above range, it is possible to stably hold the solid graphite particles, etc.

[0061] When a conductive agent is used in the negative electrode active material layer, the proportion of the conductive agent in the entire negative electrode active material layer can be about 10 mass % or less, and usually, it is preferably about 8.0 mass % or less (for example, 3.0 mass % or less). The technology disclosed herein can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain the conductive agent.

[0062] When a thickener is used in the negative electrode active material layer, the proportion of the thickener in the entire negative electrode active material layer can be approximately 8 mass % or less, and usually is preferably approximately 5.0 mass % or less (for example, 1.0 mass % or less).

[0063] When a filler is used in the negative electrode active material layer, the proportion of the filler in the entire negative electrode active material layer can be about 8.0 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less). The technology disclosed herein can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain the above-mentioned filler.

[0064] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, binder, conductive agent, thickener, and filler.

[0065] The negative electrode active material layer is preferably disposed on the negative electrode substrate directly or via another layer without being pressed. The ratio (R2 / R1) of the surface roughness R2 of the negative electrode substrate in the region where the negative electrode active material layer is not laminated to the surface roughness R1 of the negative electrode substrate in the region where the negative electrode active material layer is laminated is preferably 0.90 or more and 1.10 or less, more preferably 0.92 or more and 1.05 or less, and even more preferably 0.94 or more. In a negative electrode in which the negative electrode active material layer is laminated on the negative electrode substrate, the stronger the negative electrode active material layer is pressed, the larger the surface roughness R1 of the region where the negative electrode active material layer is laminated on the negative electrode substrate becomes, and therefore the ratio (R2 / R1) of the surface roughness R2 of the region where the negative electrode active material layer is not laminated becomes smaller. In other words, when no pressing is performed, the surface roughness of the region of the negative electrode substrate where the negative electrode active material layer is disposed and the region where the negative electrode active material layer is not disposed (for example, the exposed region of the negative electrode substrate when the negative electrode substrate is exposed in the negative electrode) will be almost the same. That is, the ratio (R2 / R1) approaches 1. That is, when the ratio (R2 / R1) is within the above range, this means that no or only small pressure is applied to the negative electrode active material layer in the state where it is laminated on the negative electrode substrate.

[0066] In this way, when the negative electrode active material layer is not pressed or when the above ratio (R2 / R1) is within the above range, the exposure of the edge faces of the solid graphite particles is reduced, thereby making it possible to further improve the output characteristics after long-term use.

[0067] The "surface roughness" of the negative electrode substrate means the arithmetic mean roughness Ra of the surface of the negative electrode substrate (for the region where the negative electrode active material layer and other layers are laminated, the surface after removing these layers) measured with a laser microscope in accordance with JIS-B0601 (2013). Specifically, it can be a measured value by the following method. First, if the negative electrode has a portion where the negative electrode substrate is exposed, the surface roughness of this portion is taken as the surface roughness R2 of the region where the negative electrode active material layer is not disposed, and is measured in accordance with JIS-B0601 (2013) using a commercially available laser microscope (manufactured by Keyence Corporation, device name "VK-8510"). At this time, the measurement conditions are a measurement region (area) of 149 μm × 112 μm (16688 μm 2 ), the measurement pitch is 0.1 μm. Next, the negative electrode is shaken using an ultrasonic cleaner to remove the negative electrode active material layer and other layers from the negative electrode substrate. The surface roughness R1 of the region where the negative electrode active material layer was laminated is measured in the same manner as the surface roughness of the portion where the negative electrode substrate is exposed. In addition, when there is no portion where the negative electrode substrate is exposed on the negative electrode (for example, when the entire surface of the negative electrode substrate is covered with an intermediate layer), the surface roughness of the region where the negative electrode active material layer was not arranged (for example, the region covered with an intermediate layer and where the negative electrode active material layer was not arranged) is measured in the same manner as the surface roughness R2 of the region where the negative electrode active material layer is not arranged. Shaking using an ultrasonic cleaner can be performed by shaking the negative electrode substrate while immersing it in water for 3 minutes and then in ethanol for 1 minute using a Branson tabletop ultrasonic cleaner "2510J-DTH".

[0068] The surface roughness R2 of the negative electrode substrate in a region where no negative electrode active material layer is laminated is, for example, 0.1 μm to 10 μm, and may be 0.3 μm to 3 μm.

[0069] The density of the negative electrode active material layer is not particularly limited, but for example, the lower limit is 0.8 g / cm 3 is preferred, and 1.0 g / cm 3 More preferably, 1.1 g / cm 3 More preferably, 1.2 g / cm 3 (For example, 1.3 g / cm3 ) is even more preferable. By making the density of the negative electrode active material layer equal to or higher than the above lower limit, it is possible to increase the energy density per volume. In addition, when solid graphite particles having a relatively small particle size are used, the negative electrode active material layer can have a high density without pressing the negative electrode active material layer, so that it is possible to increase the energy density per volume and improve the output characteristics after long-term use. On the other hand, the upper limit of the density of the negative electrode active material layer is, for example, 1.8 g / cm. 3 is preferred, and 1.6 g / cm 3 (For example, 1.55 g / cm 3 ) is more preferable, and 1.5 g / cm 3 (For example, 1.45 g / cm 3 ) is more preferred.

[0070] The average thickness of the negative electrode active material layer (when the negative electrode active material layer is formed on both sides of the negative electrode substrate, the total thickness of both sides) is not particularly limited, but for example, the lower limit is preferably 30 μm, more preferably 40 μm, and even more preferably 50 μm. On the other hand, the upper limit of the average thickness of the negative electrode active material layer is, for example, preferably 220 μm, more preferably 200 μm, and even more preferably 180 μm. In some embodiments, the upper limit of the average thickness of the negative electrode active material layer may be, for example, 150 μm, and typically may be 120 μm (for example, 100 μm, 80 μm, or 60 μm). In a nonaqueous electrolyte storage element having a negative electrode active material layer having the above average thickness, the application effect of this embodiment can be more suitably exhibited.

[0071] [Separator] The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0072] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500° C. in an air atmosphere at 1 atm, and more preferably have a mass loss of 5% or less when heated from room temperature to 800° C. in an air atmosphere at 1 atm. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As inorganic compounds, these substances may be used alone or in combination. Among these inorganic compounds, silicon oxide, aluminum oxide, and aluminosilicates are preferred from the viewpoint of the safety of the storage element.

[0073] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0074] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0075] [Non-aqueous electrolyte] The nonaqueous electrolyte includes an unsaturated cyclic carbonate. The nonaqueous electrolyte may be a nonaqueous electrolytic solution that further includes, in addition to the unsaturated cyclic carbonate, another nonaqueous solvent and an electrolyte salt.

[0076] The unsaturated cyclic carbonate is a cyclic carbonate having a carbon-carbon unsaturated bond in the molecule, and is a component added as a component that forms a coating that covers the surface of solid graphite particles, etc. A part of the unsaturated cyclic carbonate added to the nonaqueous electrolyte used in manufacturing the nonaqueous electrolyte storage element decomposes to form the above-mentioned coating during initial charge and discharge, but the unsaturated cyclic carbonate that is not decomposed during the initial charge and discharge remains in the nonaqueous electrolyte.

[0077] The unsaturated cyclic carbonate may be a cyclic carbonate having a carbon-carbon double bond in the molecule. The unsaturated cyclic carbonate may be a cyclic carbonate having a carbon-carbon double bond in the ring structure, a cyclic carbonate having a carbon-carbon double bond in a portion other than the ring structure, etc. The unsaturated cyclic carbonate may be one in which a part or all of the hydrogen atoms are replaced with other groups or elements.

[0078] Examples of cyclic carbonates having a carbon-carbon double bond in the ring structure include vinylene carbonate, fluorovinylene carbonate, methylvinylene carbonate, fluoromethylvinylene carbonate, ethylvinylene carbonate, propylvinylene carbonate, butylvinylene carbonate, dimethylvinylene carbonate, diethylvinylene carbonate, dipropylvinylene carbonate, trifluoromethylvinylene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate.

[0079] Examples of cyclic carbonates having a carbon-carbon double bond in a portion other than the ring structure include vinyl ethylene carbonate and styrene carbonate.

[0080] As the unsaturated cyclic carbonate, a cyclic carbonate having a carbon-carbon double bond in the ring structure is preferable, and vinylene carbonate is more preferable.

[0081] The concentration of the unsaturated cyclic carbonate in the non-aqueous electrolyte (i.e., the remaining concentration of the unsaturated cyclic carbonate not decomposed during the initial charge and discharge) is, for example, preferably from 0.1% by mass to 5% by mass, more preferably from 0.2% by mass to 3% by mass, and even more preferably from 0.3% by mass to 1% by mass.

[0082] The lower limit of the amount of unsaturated cyclic carbonate with respect to the surface area of ​​the negative electrode active material layer is 0.03 mmol / m 2 and 0.04 mmol / m 2 is preferred, and 0.05 mmol / m 2 or 0.06 mmol / m 2 By setting the amount of the unsaturated cyclic carbonate to the surface area of ​​the negative electrode active material layer to be equal to or greater than the above lower limit, a sufficient coating film can be formed, and output characteristics can be improved after long-term use. On the other hand, the upper limit of the amount of the unsaturated cyclic carbonate to the surface area of ​​the negative electrode active material layer is 0.08 mmol / m 2 and 0.07 mmol / m 2is preferred, and 0.06 mmol / m 2 or 0.05 mmol / m 2 By setting the amount of the unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer to be equal to or less than the above upper limit, it is possible to prevent the coating film formed during initial charge / discharge from becoming too thick, and as a result, the output characteristics immediately after the initial charge / discharge are improved, and the output characteristics remain high even after long-term use.

[0083] As the other non-aqueous solvent, a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element can be used. As the other non-aqueous solvent, cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, nitriles, etc. can be mentioned. Note that the cyclic carbonates as the other non-aqueous solvents do not include unsaturated cyclic carbonates.

[0084] As the other non-aqueous solvent, it is preferable to use at least one of cyclic carbonate and chain carbonate, and it is more preferable to use cyclic carbonate and chain carbonate in combination. When using cyclic carbonate and chain carbonate in combination, the volume ratio of cyclic carbonate to chain carbonate (cyclic carbonate: chain carbonate) is not particularly limited, but is preferably, for example, 5:95 to 50:50.

[0085] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), chloroethylene carbonate, fluoroethylene carbonate (FEC), and difluoroethylene carbonate (DFEC).

[0086] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate.

[0087] The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte for a storage element, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.

[0088] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a hydrocarbon group in which hydrogen is replaced by fluorine such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0089] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte is 0.1 mol / dm 3 is preferred, and 0.3 mol / dm 3 More preferably, 0.5 mol / dm 3 More preferably, 0.7 mol / dm 3 On the other hand, the upper limit is not particularly limited, but is preferably 2.5 mol / dm 3 is preferred, and 2 mol / dm 3 More preferably, 1.5 mol / dm 3 is more preferred.

[0090] The non-aqueous electrolyte may contain other additives. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexyl benzene, and cyclohexyl benzene. hexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.

[0091] The content of additives (components other than unsaturated cyclic carbonate, other nonaqueous solvents, and electrolyte salt) contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of additives within the above range, it is possible to improve the capacity retention performance or charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0092] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a pouch film battery, a square battery, a flat battery, a coin battery, and a button battery.

[0093] FIG 1 shows an electricity storage element 1 (nonaqueous electrolyte electricity storage element) as an example of a prismatic battery. Note that this figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0094] <Configuration of Nonaqueous Electrolyte Electricity Storage Device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as a storage device configured by assembling a plurality of storage elements 1 in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source. In this case, the technology of the present invention may be applied to at least one storage element included in the storage device. In a preferred embodiment, the storage device includes the storage element according to the above-mentioned embodiment, a detection unit, and a control unit. The detection unit detects the voltage between the positive electrode and the negative electrode of the storage element. The detection unit can be a conventionally known voltmeter, voltage sensor, or the like. The control unit is electrically connected to the detection unit and configured to stop charging the storage element when the voltage detected by the detection unit is equal to or higher than a predetermined value. For example, when charging using a charger, the control unit can be configured to cut off the electrical connection between the charger and the storage element when the voltage becomes equal to or higher than a predetermined value. The control unit can be configured to be a computer and a computer program. In addition, the control unit may be configured to be a processor, part or all of which is made of a semiconductor chip. In one embodiment of the power storage device, when the voltage of the power storage element is the predetermined value, the potential of the positive electrode is 4.2 V (vs. Li / Li + ) or less. That is, when charging is stopped, the potential of the positive electrode is 4.2V (vs. Li / Li+ The potential of the positive electrode when the charging of the storage element is stopped by the control unit is preferably 4.1 V (vs. Li / Li + ) or less, more preferably 4V (vs. Li / Li + In some embodiments, the potential of the positive electrode when the charging of the power storage element is stopped by the control unit is, for example, 3.8 V (vs. Li / Li + ) or less, and 3.7V (vs. Li / Li + In an electricity storage device in which the potential of the positive electrode when charging is stopped is set as described above, the above-mentioned effects can be more effectively exhibited.

[0095] 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects the two or more energy storage elements 1, a bus bar (not shown) that electrically connects the two or more energy storage units 20, and the like. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more energy storage elements.

[0096] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte electricity storage element according to one embodiment of the present invention is not particularly limited, but for example, the following production method can be adopted.

[0097] The manufacturing method includes preparing a negative electrode having a negative electrode active material layer containing solid graphite particles having an aspect ratio of 1 or more and 5 or less, preparing a non-aqueous electrolyte containing an unsaturated cyclic carbonate, and performing initial charging and discharging of an uncharged and discharged energy storage element assembled using the negative electrode and the non-aqueous electrolyte.

[0098] The step of preparing the negative electrode can be performed, for example, by applying a negative electrode mixture to a negative electrode substrate, and laminating a negative electrode active material layer along at least one surface of the negative electrode substrate. Specifically, for example, the negative electrode substrate can be coated with a negative electrode mixture and dried to laminate the negative electrode active material layer.

[0099] The negative electrode mixture contains the solid graphite particles. The negative electrode mixture may be a negative electrode mixture paste containing a dispersion medium in addition to the solid graphite particles and each optional component constituting the negative electrode active material layer. The dispersion medium may be an organic solvent such as N-methylpyrrolidone (NMP) or toluene, or water.

[0100] The method preferably does not include pressing the negative electrode active material layer. For example, the method may include a step of preparing a negative electrode having an unpressed negative electrode active material layer.

[0101] In the step of preparing the non-aqueous electrolyte, for example, the components constituting the non-aqueous electrolyte, such as the unsaturated cyclic carbonate, the electrolyte salt, and other non-aqueous solvents, are mixed together to prepare the non-aqueous electrolyte.

[0102] The manufacturing method may further include preparing a positive electrode, stacking the positive electrode and the negative electrode with a separator interposed therebetween to obtain an electrode body, housing the electrode body in a container, injecting a non-aqueous electrolyte into the container, etc. Thereafter, an uncharged and discharged electricity storage element is obtained by sealing the inlet.

[0103] The obtained uncharged and discharged electric storage element is charged and discharged once or multiple times as an initial charge and discharge. As a result, a part of the unsaturated cyclic carbonate in the nonaqueous electrolyte prepared in the step of preparing the nonaqueous electrolyte is decomposed, and a coating is formed on the particle surface of the negative electrode active material. Through such a process, the amount of the unsaturated cyclic carbonate contained in the nonaqueous electrolyte relative to the surface area of ​​the negative electrode active material layer becomes 0.03 mmol / m 2 More than 0.08mmol / m 2 The following nonaqueous electrolyte electricity storage element is obtained.

[0104] The amount of the unsaturated cyclic carbonate contained in the nonaqueous electrolyte relative to the surface area of ​​the negative electrode active material layer is adjusted by the concentration of the unsaturated cyclic carbonate in the nonaqueous electrolyte prepared in the step of preparing the nonaqueous electrolyte, the amount of the nonaqueous electrolyte, the amount and size (surface area) of the solid graphite particles, etc.

[0105] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above embodiment. In the above embodiment, the nonaqueous electrolyte storage element is mainly described as a nonaqueous electrolyte secondary battery, but other nonaqueous electrolyte storage elements may be used. Examples of other nonaqueous electrolyte storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc. EXAMPLES

[0106] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0107] [Example 1] (Preparation of negative electrode) Graphite particles A as negative electrode active material (lumpy solid graphite, aspect ratio 3.0, average particle size 3.0 μm, BET specific surface area 3.9 m 2 A negative electrode mixture paste was prepared containing 100% cellulose acetate (CO2) and 100% cellulose acetate (CO2) (100% by weight), styrene butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. The ratio of the negative electrode active material, binder, and thickener was 96:3.2:0.8 by mass. The negative electrode mixture paste was applied to both sides of copper foil with an average thickness of 8 μm as a negative electrode substrate, and dried to form a negative electrode active material layer, thereby obtaining a negative electrode. The negative electrode active material layer was not pressed. The ratio (R2 / R1) of the surface roughness R2 of the negative electrode substrate in the region where the negative electrode active material layer is not laminated to the surface roughness R1 of the negative electrode substrate in the region where the negative electrode active material layer is laminated was 0.97. The average thickness of the negative electrode active material layer (both sides combined) was 54 μm, and the density was 1.37 g / cm 3The area ratio of graphite particle A, excluding voids within the particles, to the total particle area was 99.1%.

[0108] (Preparation of positive electrode) An intermediate layer paste was prepared containing acetylene black as a conductive agent, hydroxyethyl chitosan as a binder, pyromellitic acid as a crosslinking agent, and N-methylpyrrolidone (NMP) as a dispersion medium. The ratio of the conductive agent, binder, and crosslinking agent was adjusted so that the mass ratio in the dried and solidified state was 1:1:1. The intermediate layer paste thus prepared was applied to both sides of an aluminum foil having an average thickness of 15 μm as a positive electrode substrate, with a coating amount of 0.05 mg / cm after drying. 2 The mixture was then dried to form an intermediate layer. A positive electrode mixture paste was prepared containing lithium iron phosphate as a positive electrode active material, polyvinylidene fluoride (PVDF) as a binder, acetylene black as a conductive agent, and N-methylpyrrolidone (NMP) as a dispersion medium. The ratio of the positive electrode active material, the binder, and the conductive agent was 91:4:5 by mass. The positive electrode mixture paste was applied to the surface of each intermediate layer formed on both sides of the positive electrode substrate, and dried. Then, the mixture was pressed to form a positive electrode active material layer. As a result, a positive electrode was obtained in which an intermediate layer and a positive electrode active material layer were laminated on both sides of the positive electrode substrate. The average thickness of the positive electrode active material layer (total of both sides) in the obtained positive electrode was 59 μm and the density was 1.94 g / cm 3 It was.

[0109] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:35:35 was added with 1.2 mol / dm lithium hexafluorophosphate (LiPF6) as an electrolyte salt. 3 To this mixed solution, vinylene carbonate (VC), which is an unsaturated cyclic carbonate, was added at a concentration of 1.50 mass % to prepare a nonaqueous electrolyte.

[0110] (Assembly of non-aqueous electrolyte storage element) The positive and negative electrodes were laminated with a 15 μm thick polyethylene microporous membrane separator and wound to produce a wound electrode body. The wound electrode body was placed in a container. The non-aqueous electrolyte was then poured into the container to obtain a non-charged / discharged electricity storage element.

[0111] (Initial charge / discharge) The obtained uncharged and discharged electricity storage element was charged at constant current and constant voltage (CCCV) in a thermostatic chamber at 25° C. for a total charging time of 3 hours under the conditions of a charging current of 1 C and a charge cut-off voltage of 3.5 V. Then, constant current (CC) discharge was performed under the conditions of a discharge current of 1 C and a discharge cut-off voltage of 2.0 V. Through the above initial charge and discharge, a nonaqueous electrolyte electricity storage element of Example 1 was obtained. The capacity checks described below were all carried out under the above conditions.

[0112] [Examples 2 to 4, Comparative Examples 1 to 10] The nonaqueous electrolyte storage elements of Examples 2 to 4 and Comparative Examples 1 to 10 were obtained in the same manner as in Example 1, except that the type of graphite particles as the negative electrode active material, whether or not pressing was performed when forming the negative electrode active material layer, the average thickness and density of the negative electrode active material layer (total of both sides), and the VC concentration of the prepared nonaqueous electrolyte were as shown in Table 1. The area ratio of graphite particles B excluding voids in the particles to the total particle area was 88.8%, and the average particle diameter was 8.8 μm. The area ratio of graphite particles C excluding voids in the particles to the total particle area was 98.5%, and the average particle diameter was 10.3 μm.

[0113] Two of each nonaqueous electrolyte storage element were prepared, one for measuring the amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer and the other for evaluating output characteristics after long-term use.

[0114] (Measurement of the amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer) For each of the non-aqueous electrolyte storage elements for disassembly analysis of the obtained examples and comparative examples, the concentration of VC (unsaturated cyclic carbonate) in the non-aqueous electrolyte and the amount of VC (unsaturated cyclic carbonate) relative to the surface area of ​​the negative electrode active material layer were measured by the above-mentioned method. The measurement results are shown in Table 1.

[0115] [evaluation] (Long-term charge / discharge cycle test) Each of the obtained nonaqueous electrolyte storage elements was charged to SOC50% in a thermostatic chamber at 25°C (after constant current constant voltage (CCCV) charging with 50% of the discharge capacity obtained in the immediately preceding capacity confirmation under the conditions of a charging current of 1C and a charging end voltage of 3.5V), and then left in a thermostatic chamber at 45°C for 4 hours to stabilize the temperature. Then, constant current (CC) charging was performed under the conditions of a charging current of 8C and a charging end voltage of 3.5V, and then constant current (CC) discharging was performed under the conditions of a discharging current of 8C and a discharging end voltage of 3.05V. This charge / discharge cycle was performed for 250 hours. No break was provided after charging and discharging. Then, the element was left in a thermostatic chamber at 25°C for 4 hours to stabilize the temperature, and then discharged under the conditions of a discharging current of 1C and a discharging end voltage of 2.0V to obtain a discharged state. Next, the capacity was confirmed under the same conditions as the above-mentioned "initial charge / discharge" and the output characteristics were measured as described below. The above 250-hour charge / discharge cycle, capacity confirmation, and output characteristic measurement were repeated until the total charge / discharge cycle time reached 3,500 hours. (Output characteristic measurement) Each nonaqueous electrolyte storage element was charged from a discharged state to an SOC of 50% in a thermostatic chamber at 25° C. with a constant current constant voltage (CCCV) charge of 50% of the discharge capacity obtained in the immediately preceding capacity check, at a charging current of 1 C and a charge cut-off voltage of 3.5 V. Output characteristics of this nonaqueous electrolyte storage element with an SOC of 50% were measured under the following conditions. The battery was discharged at a constant current (CC) of 5C for 10 seconds, and after a 60-second pause, it was charged at a constant current (CC) of 0.5C with the same amount of electricity as the amount of electricity discharged, and then paused for 300 seconds. After that, tests were performed at each current value under the same conditions except that the discharge current value was changed to 10C, 15C, 20C, and 25C. The measured values ​​of each discharge current value (5C, 10C, 15C, 20C, and 25C) were plotted on the horizontal axis and the voltage 1 second after the start of discharge on the vertical axis. Linear approximation was performed on these plots by using the least squares method. The absolute value of the slope of the straight line was taken as the resistance R [Ω] of the nonaqueous electrolyte storage element. Based on the calculated resistance R, the outputtable power P [W] of the nonaqueous electrolyte storage element was calculated using the following (Equation 1), and was taken as the "output characteristic [W]". P=V min ×(V 50 -V min ) / R (Equation 1) Here, V min means the lower limit of the expected operating voltage per nonaqueous electrolyte storage element. In all examples and comparative examples, V min A voltage of 2.63 V was used. 50 V means the open circuit voltage at SOC 50%. 50 The voltage immediately before 5C discharge was rounded off to two decimal places and used as the value up to two decimal places. The output characteristics measured after a total charge / discharge cycle time of 3,500 hours are shown in Table 1. The results of Examples 1 to 4 and Comparative Examples 1 to 3 using graphite particles A (solid graphite particles with an aspect ratio of 3) and Comparative Examples 4 to 7 using graphite particles B (hollow graphite particles with an aspect ratio of 1.6) are shown in FIG.

[0116] [Table 1]

[0117] As shown in Table 1, solid graphite particles with a small aspect ratio (graphite particles A) were used, and the amount of VC relative to the surface area of ​​the negative electrode active material layer was 0.03 mmol / m 2 More than 0.08mmol / m 2In each of the nonaqueous electrolyte storage elements in Examples 1 to 4 described below, the output characteristics after the long-term charge-discharge cycle test were high and exceeded 700 W. On the other hand, even when solid graphite particles (graphite particles A) with a small aspect ratio were used, the amount of VC was 0.03 mmol / m 2 Less than or equal to 0.08mmol / m 2 In the nonaqueous electrolyte storage elements of Comparative Examples 1 to 3, which contained more graphite particles, and the nonaqueous electrolyte storage elements of Comparative Examples 4 to 10, which used hollow graphite particles (graphite particles B) or solid graphite particles with a large aspect ratio (graphite particles C), the output characteristics after the long-term charge-discharge cycle test were 700 W or less. 2 More than 0.08mmol / m 2 It has been confirmed that by satisfying the following conditions, a nonaqueous electrolyte electricity storage element having high output characteristics even after long-term use can be obtained.

[0118] In addition, as shown in FIG. 3, when solid graphite particles (graphite particles A) are used, the range of the amount of unsaturated cyclic carbonate in which the output characteristics are deteriorated when hollow graphite particles (graphite particles B) are used (the amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer is 0.03 mmol / m 2 More than 0.08mmol / m 2 In contrast, when the graphite particles had a specific shape, the output characteristics improved when the graphite particles had a specific amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer. This is believed to be due to the fact that the thickness and uniformity of the coating film formed by the decomposition of the unsaturated cyclic carbonate vary depending on the shape of the graphite particles. In other words, the effect of having high output characteristics even after long-term use is believed to be a specific effect produced by combining graphite particles having a specific shape with a specific range of the amount of unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer. [Industrial Applicability]

[0119] The present invention is suitably used as an electricity storage element, including a non-aqueous electrolyte secondary battery used as a power source for electronic devices such as personal computers and communication terminals, automobiles, and the like. [Explanation of symbols]

[0120] 1 Energy storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. a negative electrode having a negative electrode active material layer; A non-aqueous electrolyte containing an unsaturated cyclic carbonate. Equipped with the negative electrode active material layer contains solid graphite particles having an aspect ratio of 1 or more and 5 or less, The amount of the unsaturated cyclic carbonate relative to the surface area of ​​the negative electrode active material layer is 0.03 mmol / m 2 0.08 mmol / m or more 2 The nonaqueous electrolyte storage element is as follows:

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the solid graphite particles have an average particle size of 2 μm or more and 6 μm or less.

3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein a content ratio of said solid graphite particles to the total negative electrode active material contained in said negative electrode active material layer is 99 mass % or more.

4. 4. The nonaqueous electrolyte storage element according to claim 1, wherein the negative electrode active material layer is not pressed.

5. A positive electrode having a positive electrode active material layer, 5. The nonaqueous electrolyte storage element according to claim 1, wherein the positive electrode active material layer contains a polyanion compound as a positive electrode active material.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and secondary battery using the same

    JP2002158035A

  • Negative pole material for lithium battery, and lithium battery

    JP2005222933A

  • Power storage device and electronic device

    JP2018092928A